Analisis Faktor-Faktor yang Mempengaruhi Kualitas Informasi Laporan Keuangan Pemerintah pada Dinas BKAD - Christine Monica Saren; Rahayu Mokoagow (Global Leadership Organizational Research in Management, 2024)
This study aims to analyze the factors that affect the quality of government financial report information at the Regional Finance and Assets Agency (BKAD). The factors studied include human resource competence, internal control, information technology utilization, and accounting understanding. Data was collected through a questionnaire distributed to BKAD employees and analyzed using the multiple linear regression method. The results of the study show that all the factors studied have a significant influence on the quality of financial statement information. These findings emphasize the importance of improving human resource competence, effective internal control, optimal use of information technology, and a good understanding of accounting in order to produce quality financial reports.